New Strait Times, 25 June 2008 (The New Straits Times Press (M) Bhd, 2008)
Nursing is one of the worlds oldest professions, and rewarding career dedicated to preventing illness, reducing suffering, assisting in the recovery of patients and effective rehabilitation of individuals and their family .